SYMBOLIC CONVERGENCE ANALYSIS OF THE DEMOCRATIC PARTY'S INSTAGRAM ACCOUNT2024 ELECTION CAMPAIGN PERIOD - Hendra Sunandar; Farid Irawan; Edison Bonartua (RADJA PUBLIKA, 2025)
This study analyzes the use of Symbolic Convergence Theory (SCT) in the digital campaign of the Democratic Party through Instagram during the 2024 election campaign. SCT, developed by Ernest Bormann, provides a framework for understanding how groups or communities create and share meaning through narratives and symbols. In this context, the study aims to identify dominant fantasy themes in the Democratic Party's Instagram content and explore how these themes are used to build group identity and solidarity. The methodology used is qualitative content analysis of the Democratic Party's Instagram posts, with primary data obtained from text, images, videos, and interactions (comments, likes, and shares) on the official Instagram account of the Democratic Party. In-depth interviews with relevant parties involved in the digital campaign, including party members and campaign staff, were also conducted to gain insights into the digital campaign strategies adopted. The results show that the Democratic Party effectively uses narratives and symbols through Instagram to build collective identity and emotional bonds with its followers. Fantasy themes such as